PERANCANGAN SISTEM MANAGEMENT E-APPROVAL BERBASIS WEB DI PT. ARWANA CITRAMULIA TBK MENGGUNAKAN REACTJS - Priyanto, Sandra; Arfian, Muhamad Hadi; Anwar, Nizirwan (ROUTERS: Jurnal Sistem dan Teknologi Informasi, 2025)
The process of creating invoices has been carried out by PT. Arwana Citramulia Tbk is currently causing delays in billing invoices to customers because it requires a long process and takes quite a long time to create invoices. Delays in billing invoices to customers will cause problems in terms of payment and repayment of purchases of products that have been sold, so that the company's receivables report will increase. The need for a Web-Based E-Approval Management System is to simplify the process of approval activities by the relevant departments for the Approval process of product invoices and to apply the paperless concept to these invoices with digital signatures. The methods used to carry out the design are Unified Modeling Language, Extreme Programming and Black-Box Testing. The results obtained show that this system can simplify the approval process for product sales invoices by division heads and managers so that signing product sales invoices can be digital and it will be easier to send invoices to customers